2020
DOI: 10.1186/s12885-020-07491-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of concomitant systemic treatments on toxicity and intracerebral response after stereotactic radiotherapy for brain metastases

Abstract: Background The aim of this study was to determine the safety and efficacy of fractionated stereotactic radiotherapy (SRT) in combination with systemic therapies (ST) for brain metastases (BM). Methods Ninety-nine patients (171 BM) received SRT and concurrent ST (group 1) and 95 patients (131 BM) received SRT alone without concurrent ST (group 2). SRT was planned on a linear accelerator, using volumetric modulated arc therapy. All ST … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…Safety of combination therapy in the literature is heterogeneous; however almost all authors agree that the putative slightly increased risk is manageable, particularly in light of the likely benefit on efficacy and survival [42,43]. In our study, 10% of the patients developed radionecrosis, which was, in most cases, reversible and manageable with transient steroid therapy and consistent with previously reported results [35]. However given this nonnegligible risk, and the difficulty of distinguishing it from local failure, multimodal MRI is strongly recommended during follow-up [44].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Safety of combination therapy in the literature is heterogeneous; however almost all authors agree that the putative slightly increased risk is manageable, particularly in light of the likely benefit on efficacy and survival [42,43]. In our study, 10% of the patients developed radionecrosis, which was, in most cases, reversible and manageable with transient steroid therapy and consistent with previously reported results [35]. However given this nonnegligible risk, and the difficulty of distinguishing it from local failure, multimodal MRI is strongly recommended during follow-up [44].…”
Section: Discussionsupporting
confidence: 90%
“…Many retrospective studies reported enhanced local control when radiotherapy was delivered in combination with immunotherapy, providing further evidence for a synergistic effect of ICIs and radiation therapy [34][35][36].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Thus, it became evident that combining local RT (e.g., SRT) with systemic IT (e.g., ICIs) might be beneficial to further improve disease control in general. For instance, albeit it remains unclear if the risk of radiation necrosis might be elevated, a clear benefit in terms of outcome has been shown for IT and stereotactic treatment for brain metastases 16 18 . Therefore, in current clinical practice, many patients with advanced stage diseases (e.g., Melanoma, Non-small cell lung cancer) receive IT either simultaneously or sequentially to RT.…”
Section: Introductionmentioning
confidence: 99%